Penerapan Kode Etik Profesi Akuntan Publik dan Kasus-Kasus Pelanggaran Etika Profesi Akuntan Publik - Arfan Wiyanto; Dini Agustiani; Katarina Apriliana Zhilda; Lydia Yohana Sitohang; Mega Utami (Universitas 45 Surabaya, 2025)
A Public Accountant is an individual who has obtained a license from the Minister of Finance to offer services in accordance with the provisions of Law Number 5 of 2011 concering Public Accountants. Public accountants are required to exhibit good behavior-being honest, responsible, and possessing high integrity. In carrying out their duties, public accountants must comply with and uphold the Public Accountant’s Profesional Standards (SPAP), the Code of Professional Ethics, and laws relevant to the services they provide. The Code of Ethics for Public Accountants serves as guideline for ethical conduct and as a guarantee of moral quality in society. However, public accountants still often commit violations despite the existence of the professional code of ethics. As a result, this may lead to scandals that damage the reputation of the public accounting profession and reduce public trust. The purpose of this article is to narratively explain how the principles and enforcement of the Code of Ethics for Public Accountants are implemented, so that audit results are consistent with the evidence found, without any accounting manipulation that could harm interested parties.